TOURISM-BASED URBAN AGRICULTURAL INTEGRATED FOOD MARKET (CASE STUDY: SINDU MARKET, SANUR, BALI) - Mahendra, I Gede Indra; Diasana Putra, I Dewa Gede Agung (ASTONJADRO, 2022)
The market is a place where basic needs such as food can be purchased. The high demand for food in Denpasar is dominated by the needs of the tourism sector and the community. The fulfillment of the need for food is highly dependent on the agricultural sector. The increasing need for food is inversely proportional to the aspect of supporting the fulfillment of needs because the condition of agricultural land in Denpasar City is decreasing every year, so it must depend on outside areas such as Tabanan Regency, Bangli and the largest imported from Java. The ability of a region to produce food that can guarantee sufficient food needs by utilizing the existing potential can achieve food independence. The application of agricultural systems to produce food in urban areas really needs to be developed to provide access to adequate food to meet food needs. This article aims to explore the potential of urban urban areas that are integrated with traditional markets in urban areas at Sindu Market. Located in the Sanur tourism sector area, Sindu Market has potential that can be directed to become a tourism-based market. Furthermore, this article aims to determine the condition of food self-sufficiency in Denpasar City and the areas that supply food needs for Denpasar City by implementing the Urban Farming system. The implementation of the Urban Farming system will shorten the carbon chain in terms of distributing food ingredients from outside Denpasar City. The research method used is qualitative with a descriptive approach. Data was collected by observation and interviews. The results showed that the food needs of the city of Denpasar were still not independent of their own food needs so that an innovative idea was born in the form of implementing the Urban Farming system at the Sindu Market, which was expected to be a solution to the problem of food needs in Denpasar City.